Cartografias do câncer: biossociabilidade, comunicação e subjetividade - Bozz, Augusto Flamaryon Cecchin (2016)
The second half of the twentieth century is highlighted as the period in which patients with cancer began to schematize collective support that, from 1970, triggered interventions in science and policy in favor of new rights to health. Before that, cancer and death were considered two areas of extreme privacy. We are leaving an increasingly "experience of illness" that segregates, excludes, as the "model of leprosy" (DELEUZE, 2005; FOUCAULT, 2013) and entering an experience sharing, associates, connects, controls the flows. Emerge "body-information" (JACOB, 1983) as the new model. On the horizon this sneaky mutation, is worth divert attention to the close relationship between the collective of patients with cancer and communication practices that constitute what Rose (2013) calls the digital biosociality. In this way, the question: what were the conditions of possibility for the correlation between the collective of patients with cancer and the new communication technologies? Our goal is to map the living conditions of the digital biosociality of cancer patients. We have used the archaeo-genealogical method (FOUCAULT, 2014a, b, c, 2010a, b, c, d, 2007) and the notion of biopower and biosociality to describe the ways of being and to be inherent power over life, creation of subject inherent in the experience of illness. We conclude that the cancer patient is a historical fabrication. This does not mean that it is fictional, but that emerges as a position of observation and "administration itself" (FOUCAULT, 2010b) correlative to the objectification of the disease, strategies to control and regulate people's health and therapeutic institutions. Concomitant with the objectification of cancer, occurs the formation of a practice of self that aims at constitute an active subject-patient, militant, activist. This subjectivity, there is look over himself and take himself that produce a certain truth about himself, a particular way of connecting to this truth and also ways and rules to drive the conduct of another patient, guide him, advise him, support him. From the 1990s, patients began to tell their stories and make activism on the Internet. This occurs because the elaboration of a device at the center of rationalization of the conduct of government strategies, putting on the scene the ethics of the association, connection and sharing. It is a reorganization of the strategies of knowledge and power, in the late twentieth century, which integrates the collective of patients with new communication technologies. Thus, it is possible to consider the communication practices, they too, as a historical fabrication operating, without doubt, in the formation of subjectivity.